Seat of Wisdom : An Introduction to Philosophy in the Catholic Tradition - Jacobs, James M. (Seminarian) (Book collections on Project MUSE., 2021)
"Seat of Wisdom is a comprehensive introduction to the philosophical principles developed in the Catholic tradition, especially as articulated in Thomism. Each of the first principles, as expressed in the transcendental properties, are then analyzed as the basis of the major philosophical disciplines. Starting with metaphysics's study of being, the argument proceeds to consider the true, the good, and the beautiful in terms of epistemology, anthropology, ethics, aesthetics, and political philosophy. Lastly, these principles are shown to point to God as creator. Other philosophical approaches are discussed and critiqued using this lens"--